Genetic Analysis of Primaquine Tolerance in a Patient with Relapsing Vivax Malaria - A. Taylor Bright (Emerging Infectious Diseases, 2013)
Patients with Plasmodium vivax malaria are treated with primaquine to prevent relapse infections. We report primaquine failure in a patient with 3 relapses without any possibility of re-infection. Using whole genome sequencing of the relapsing parasite isolates, we identified single nucleotide variants as candidate molecular markers of resistance.